Agronomic and Economic Evaluation of Compound Fertilizer Application on Cabbage (Brassica oleracea L.) - Furqoni, Hafith (WBS Laboratory, 2025)
Cabbage (Brassica oleracea L.) is a high-value vegetable crop that requires balanced nutrient management to achieve optimal growth and yield. This study aimed to evaluate the agronomic and economic effectiveness of a compound fertilizer containing 21% N, 17% P₂O₅, and 17% K₂O on cabbage production. The experiment was conducted using a randomized complete block design with seven fertilization treatments, including a control, a reference NPK treatment, and five levels of compound fertilizer (0.5 to 1.5 recommended doses), each replicated four times. Observations included plant height, leaf number, yield per plant, yield per plot, and yield per hectare. Statistical analysis was performed using ANOVA and Duncan’s Multiple Range Test at a 5% significance level, while economic analysis was based on profit and benefit-cost ratio (R/C). The results showed that the 1.0 dose of compound fertilizer significantly improved plant height at 3 and 4 weeks after transplanting, increased leaf number at 5 weeks, and produced the highest yield per plant (1.92 kg), per plot (43.8 kg), and per hectare (17,500 kg). This treatment also demonstrated the highest relative agronomic effectiveness (139%) and economic viability, with an R/C ratio of 2.23 and a profit of IDR 14,487,900. Based on these findings, the recommended application rate for cabbage is 211 kg/ha of compound fertilizer, applied one week after transplanting. The study concludes that compound fertilizer is both agronomically effective and economically profitable for cabbage cultivation under the tested conditions.